Decision tree approach based green flow-drilling of hybrid aluminium matrix composites using eco-friendly coolants. (August 2022) - Hynes, N. Rajesh Jesudoss; Sankaranarayanan, R.; Sujana, J. Angela Jennifa; Krolczyk, G.M.; Ene, Antoaneta
Abstract: Green Flow-drilling is eco-friendly and has benefits such as swift execution, clean drilling, chip-free machining and easy handling which attract manufacturers from aerospace and automotive industries in the recent years. Moreover, reinforcements in aluminium-matrix composites makes drilling more complicated in conventional drilling, because of their abrasive nature. In the present work, Green flow-drilling is employed as an effective alternative for conventional drilling process on hybrid aluminium-matrix composites. Eco-friendly coolant assisted flow-drilling is envisaged to overcome the machining challenges and to accomplish uniform heat distribution across the bushing region. Various eco-friendly coolants such as rose water solution, fenugreek solution, coconut water, buttermilk solution, coconut water/fenugreek solution and buttermilk/fenugreek solution are considered. Influences of all pre-fixed input parameters on bush-length are studied employing decision tree approach that trains the experimental data and provides potential inferences for the manufacturing benefits. In specific, fenugreek solution exhibits superior temperature reduction in comparison to other eco-friendly cooling approaches irrespective of drill-rotating speeds. The application of fenugreek solution reduced the peak-drilling temperature at 216.3 °C, 317.3 °C, 376.7 °C and 439.1 °C for 550 rpm, 900 rpm, 1350 rpm and 2100 rpm respectively without disturbing the length and quality of bush. Moreover, decision tree provides wide-ranging options to select other eco-friendly cutting fluids and drill-rotating speed for targeted response (output) parameters in the flow-drilling process. Graphical abstract: Unlabelled Image Highlights: Green Flow drilling is successful deployed on hybrid aluminium-matrix composites. Potentials of fenugreek solution and various eco-friendly coolant are explored in flow drilling applications. Effective bush-length is accomplished in hybrid aluminium-matrix composites flow drilling. Decision tree approach for judicial selection of flow drilling processing conditions